Integrating ICT in education: A scoping review of pre-service teachers’ ICT beliefs - Honghuan Li (PLoS ONE, 2025)
This scoping review aims to map the current understanding of pre-service teachers’ beliefs about ICT, identify critical research gaps, and provide actionable insights for teacher education policy and practice. A comprehensive search of seven electronic databases yielded 1366 studies, of which 277 were included. The review identified seven key themes, including a predominant focus on general ICT beliefs and the limited exploration of cutting-edge technologies or regional variations. Quantitative methods dominated the research landscape, often employing standardized instruments like the Technology Attitude Scale. The findings highlight the need for greater emphasis on underrepresented regions, innovative technologies, and qualitative methodologies to deepen contextual understanding. This review offers a foundational resource for stakeholders in teacher education and sets the stage for future research to bridge identified gaps, ultimately enhancing the integration of ICT in teacher training and classroom practice.